Manto project - design for social inclusion in Póvoa de Lanhoso - Trigueiros, Paula (2020)
MANTO (meaning mantle) is the name of an activity dedicated to social integration through design, carried out between May and July 2018, within the framework of the project Generation Lanhoso. This project takes part in an integrative program encompassing a set of activities which highlights solidarity upcycling initiatives to promote sustainable consumption of eco-friendly products, useful and accessible to all, as well as economic integration. It supports the creation of sustainable occupations for populations that are somehow disadvantaged (particularly women) and highlights handcraft knowledge. The foreseeable activities support their training to allow them to evolve in their work, gain competencies and develop their environmental awareness.